Analisis Usaha Peternakan Sapi Limosin di Desa Sei Alim Ulu Kecamatan Air Batu Kabupaten Asahan (Studi Kasus : Usaha Milik Bapak Siddiq) - Adhiana Diana ana (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
This study aims to analyze the feasibility of Mr. Siddiq's Limousine cattle farming business in Sei Alim Ulu Village, Air Batu District, Asahan Regency. This business was established in 2014 and is still operating today. Profit analysis is carried out by calculating the total costs (fixed costs and variable costs), revenue, and business profits. Meanwhile, to analyze the business, it can be calculated using the Revenue Cost Ratio (R/C Ratio) formula. The results of the study show that Mr. Siddiq's Limousine cattle farming business is as follows: Mr. Siddiq's Limousine cattle farming business made sales in January and June 2024. The total business costs consist of fixed costs of IDR 33,428,357 per year and variable costs of IDR 172,995,000, so that the total costs incurred are IDR 297,650,000. The sales results of Limousin cattle in January 2024 were IDR 94,900,000, while in June 2024 it was IDR 240,900,000. With a total income of IDR 335,800,000, this business earned a net profit of IDR 38,150,000. The Revenue Cost Ratio (R/C Ratio) value shows a value of 1.12, which means that this livestock business is profitable and feasible to develop. Keywords: Business Analysis, Limousin Cattle, Profit